Pengaruh Inovasi dan Strategi Diferensiasi terhadap Kinerja Pemasaran (Studi Pada UMKM Di Kota Banjarmasin) - Sulastini; Asmaji Adrmawi (Business Administration, FISIP ULM, 2022)
ABSTRACT : The long-term goal of UMKM development is crucial considering that UMKMs have such an important role for the economic growth of a country, including in Indonesia. UMKMs in Indonesia have contributed to the absorption of labor, the magnitude of this contribution, shows that UMKM have the ability to strengthen the structure of the national economy. The success of UMKM can be seen from the results of the performance of these UMKM. Research conducted on companies include H. Tawas, C.Djodjobo, M. Muafi Štefko R., Steffek V., 2018. Specific targets to be achieved to produce superior marketing performance, supported by innovation and differentiation strategies for the sustainability of the business being run. The purpose of this study is to determine the influence of innovation and differentiation strategies on marketing performance in sasirangan UMKM in Banjarmasin. The population in this study is UMKM in Banjarmasin. The number of samples in this study was 50 respondents using saturated samples. The method of data collection uses documentation and questionnaires. Data analysis using multiple regression version 25. The results of the study with multiple regression analysis, showed that this research model with innovation variables and Differentiation Strategies to marketing performance was fit-acceptable. The hypotheses proposed in this study there are 3 hypotheses. The activity plan proposed in the study aims to provide information that better interaction and relationships are side effects to provide space for UMKMs to innovate and differentiation strategies can still accommodate existing problems. The conclusion of this study proves that innovation and differentiation strategies have an influence on marketing performance, in order to continue to improve superior marketing performance Keywords: Innovation,Differentiation Strategy, Marketing performance